Insulin-Like Growth Factor-I (IGF-I) from Crossbred Pregnant MareSerum to Increase Follicle Number of Mice (Mus musculus) - Abdullah, Abdullah; IRestiadi, Tjuk; Lastuti, Nunuk DR; Damayanti, Tita; Wurlina, Wurlina; Safitri, Erma (KnE Life Sciences, 2017)
The purpose of the research was to know the effect of Insulin-Like Growth Factor-I (IGF-I) derived from pregnant crossbred mare serum (PMS) in mice (Mus musculus) folliculogenesis. The subjects of this research were 20 female mice. The research was arranged by Completely Randomized Design (CRD) with four treatments and five replications. The treatments were C0 = 10 ng/ml of physiological NaCl, P1 = 10 ng/ml of IGF-I PMS, P2 = 20 ng/ml of IGF-I PMS, and P3 = 40 ng/ml of IGF-I PMS. Observed variables are the number of primary, secondary, tertiary and de Graff follicles. During the treatment, the estrous cycle was also observed. The data of follicles number were analyzed by Analysis of Variance (ANOVA) and followed by HSD (Honestly Significant Difference) test. The result showed that the addition of IGF-I PMS significantly affects (p<0.05) on increasing the primary and secondary follicles number. The addition of IGF-I PMS 20 ng/ml and 40 ng/ml can increase the primary and secondary follicles significantly (p<0.05). Keywords: IGF-I crossbreed mare serum pregnant; follicle; Mus musculus